Indian dye yielding plants: Efforts and opportunities. (19th February 2021) - Aggarwal, Shilpi
Abstract: The present review article deals with the information on the dye‐yielding plants of India. Dyes are intensively coloured compounds that are applied to a substrate such as fibre, paper, cosmetics, hair, etc. to give colours and can be extracted from the roots, fruits/berries, bark, leaves, flowers, and stem/wood, fungi, and lichens by various processes of extractions. In addition to their dye‐yielding characteristics, many of these plants possess medicinal values and can be used for multiple other purposes. Plant derived‐colours have an important role in human life because of their safe and eco‐friendly nature. But due to the availability of economically cheaper synthetic dyes, the indigenous knowledge of extraction, processing, and proper utilisation has been diminished. Nowadays, the demand for natural dyes has been increased worldwide due to awareness about their beneficial properties. It has been essential that proper documentation and measure of conservation should be undertaken to preserve these natural dye‐yielding plants. This review article is an aid to a collective inquiry into Indian dye plants.